MOLECULAR BEAM EPITAXY GROWTH OF HIGH-QUALITY InN NANORODS ON Si (111) SUBSTRATE (FUDMA JOURNAL OF SCIENCES, 2024)
The growth of high-quality InN nanorods (NRs) on Si (111) by plasma-assisted molecular beam epitaxy (PAMBE) is reported.  X-ray diffraction and Raman spectroscopy investigations indicates that the NRs are wurtzite, c-axis oriented and single crystalline. Low temperature photoluminescence emissions with peak energy of ~ 0.75eV was observed indicating the high quality of the nanostructures. This study unravels a novel strategy for the successful growth of high-quality InN NRs on Silicon which is highly promising for applications in next generation nanodevices.
Keywords: InN Nanorods; Si(111); Improved quality; XRD; Raman Spectroscopy